New Horizontal Inequalities in German Higher Education? Social Selectivity of Studying Abroad between 1991 and 2012. (April 2016) - Netz, Nicolai; Finger, Claudia
On the basis of theories of cultural reproduction and rational choice, we examine whether access to study-abroad opportunities is socially selective and whether this pattern changed during educational expansion. We test our hypotheses for Germany by combining student survey data and administrative data on higher education entry rates. We find that studying abroad was socially selective during the entire observation period. Selectivity increased between 1991 and 2003 and hardly changed thereafter. Unexpectedly, the expansion of higher education does not explain this development. We also find that students from a high social background are more likely to choose exclusive types of stays abroad, that is, prolonged stays and stays funded through study-abroad scholarships. Regarding access to scholarships, social inequality increased as studying abroad became less exclusive. High-background students thus seem to replace their prior practices with more exclusive study-abroad practices.